Characterization of an entrained flow reactor for pyrolysis of coal and biomass at higher temperatures. (15th September 2015) - Tchapda, Aime H.; Pisupati, Sarma V.
Highlights: Use of CFD in the design of high pressure entrained flow reactor. Biomass residence time was higher than coal particle. Tar release was higher for biomass than from coal. Specific surface areas of coal char lower due to pore coalescence. Char showed less thermal annealing for biomass compared to coal. Abstract: A laboratory-scale entrained flow reactor for gasification/pyrolysis of coal and biomass has been designed and constructed at the Pennsylvania State University. The pre-experimental numerical simulations have been used as an aid in the design of the reactor as well as understanding and explaining the experimental results. Post experimental modeling of the reactor has been carried out using the CFD package ANSYS-Fluent. Results from experiments conducted with the reactor are here presented. These initial characterization activities of the entrained flow reactor are carried out at atmospheric pressure. Modeling and experiments are conducted at three different temperatures: 1573 K, 1673 K and 1773 K. The CFD models show some particle and gas recirculation at the inlet of the reactor. The calculated residence time in the reactor is 0.5 s for biomass and 0.4 s for coal when the particles traveling distance is 0.65 m. Tar and CO are the dominant species at 1573 K in both coal and biomass conversions, however while tar reduces as the temperature increases, the CO formation increases. Fuel conversion varies significantly between coal and biomass. The minimum conversions observed during experiments were 86.7% for biomass and 56.8% for coal at 1573 K. Conversion rates as high as 90.5% were observed for biomass at 1773 K, while the maximum coal conversion observed was 64.0% at 1773 K. The BET surface area of coal chars obtained at 1573 K and 1673 K was similar and higher than that of the char obtained at 1773 K. This drop of surface area at 1773 K has been attributed to pore coalescence, following observation of the SEM images. The surface area of biomass chars does not vary significantly. The reactivity studies conducted on the chars reveal some thermal annealing at higher temperature for coal; this occurrence is observed to be less pronounced for biomass chars.